Electrical Impedance Tomography Monitoring of Bronchoalveolar Lavage in Patients With Acute Respiratory Distress Syndrome. Issue 3 (March 2022) - Franchineau, Guillaume; Chommeloux, Juliette; Pineton de Chambrun, Marc; Lebreton, Guillaume; Bréchot, Nicolas; Hékimian, Guillaume; Bourcier, Simon; Le Guennec, Loïc; Luyt, Charles-Edouard; Combes, Alain; Schmidt, Matthieu
Abstract : OBJECTIVES: The impact of bronchoalveolar lavage on regional ventilation in mechanically ventilated patients with acute respiratory distress syndrome has rarely been described. Our objectives were use electrical impedance tomography to describe lung impedance variation post bronchoalveolar lavage and identify morphologic patterns according to respiratory failure severity. DESIGN: Monocenter physiologic study on mechanically ventilated patients. SETTING: University medical ICU. INTERVENTIONS: After a recruitment maneuver, tidal impedance variation distributions (a surrogate for impact of bronchoalveolar lavage on tidal volume distribution), end-expiratory lung impedance (correlated with end-expiratory lung volume and used to quantify postbronchoalveolar lavage derecruitment), respiratory mechanics, and blood gases were recorded before and over 6 hours post bronchoalveolar lavage with PaO2 to the FIO2 ratio. Patients were grouped according to their prebronchoalveolar lavage, that is, PaO2 to the FIO2 ratio less than 200 or greater than or equal to 200. RESULTS: Twenty-one patients (median [interquartile range] age 55 yr [50–58 yr]; 13 males), 13 with PaO2 to the FIO2 ratio less than 200, were included. Unlike that latter group, bronchoalveolar lavage significantly impacted tidal impedance variation distribution in patients with PaO2 to the FIO2 ratio greater than or equal to 200, with a ventilation shift to the contralateral lung (from 54% to 42% in the bronchoalveolar lavage side), which persisted up to 6 hours post bronchoalveolar lavage. Similarly, end-expiratory lung impedance was less distributed in the bronchoalveolar lavage side post procedure of patients with PaO2 to the FIO2 ratio greater than or equal to 200, but the difference did not reach statistical significance ( p = 0.09). As reported for tidal impedance variation, end-expiratory lung impedance distribution in patients with severe or moderate acute respiratory distress syndrome did not change significantly during the 6 hours post bronchoalveolar lavage. Although bronchoalveolar lavage effects on gas exchanges were minor in all patients, static compliance in patients with PaO2 to the FIO2 ratio greater than or equal to 200 was significantly lower post bronchoalveolar lavage ( p = 0.04). CONCLUSIONS: The negative impact of bronchoalveolar lavage on regional ventilation, which persisted at least 6 hours, appeared to be more profound in patients with normal lung function or mild acute respiratory distress syndrome. In contrast, regional ventilation, lung recruitment, respiratory mechanics, and gas exchanges were modestly impacted by the bronchoalveolar lavage in patients with severe or moderate acute respiratory distress syndrome. That finding is reassuring and supports not summarily proscribing bronchoalveolar lavage for the most severely ill with acute respiratory distress syndrome.